Ravnanje zastopnika v nasprotju interesov - kakšna je civilnopravna sankcija za zastopniški posel v primeru, ko mladoletnika pri sklenitvi ne zastopa kolizijski skrbnik, pa bi ga moral - Cvahte, Ambrož (Podjetje in delo, 2021)
In Case II Ips 54/2019, the Supreme Court of the Republic of Slovenia enforced a new position, according to which a contract concluded on behalf of a minor by one of the parents, even though it should be concluded by a collision guardian due to the conflict of interest, is voidable. In the article, we present a critique of arguments that the Court used to justify the sanction of voidability. The Court did not take into consideration the principle of abstractness in agency law, which demands conditioning the sanctions imposed by the conduct of an agent, who is in conflict of interest, with the existence of a subjective element on the part of the respective contracting party. In addition, the provisions of Art. 72 and 73 of the Obligations Code, which regulate situations of exceeding the authority and representation by an unjustified person, were overlooked. We present the provisions of Art. 213 of the Marriage and Family Relations Act and Art. 269 of the Family Code, which regulate the issue of a collision guardian, but do not determine the legal consequences for agency transactions that are not concluded by the collision guardian, although they should be. In our view, those consequences should be assessed in accordance with the general system of rules governing the conduct of an agent in a conflict of interest.
Keywords: abuse of authority; agency; collision agent; collision guardian; collision of interest; conflict of interest; izpodbojnost; kolizija interesov; kolizijski skrbnik; kolizijski zastopnik; nasprotje interesov; voidability; zastopanje; zloraba zastopniške moči